The role of women in seaweed aquaculture in the Western Indian Ocean and South-East Asia. Issue 4 (2nd October 2017) - Msuya, Flower E.; Hurtado, Anicia Q.
ABSTRACT: In most developing countries, the majority of people involved with seaweed farming are women. Their immense contribution to the industry has been widely demonstrated and evaluated in successful examples/case studies. These 'seaweed women' have made significant advances in the sustainability of seaweed farming for more than four decades and their dedication, patience and resilience illustrate tenacity in the face of crises. The roles of women are complex, including hands-on farming activities as well as small-scale processing to produce value-added products based on the seaweed biomass cultivated. We detail the role of women in seaweed aquaculture in the Western Indian Ocean (WIO, including Africa and India) and South-East Asia. In Africa, there are significantly more women than men employed, and their roles are more varied, whilst in South-East Asia, men and women are involved in almost equal numbers at the various levels of the seaweed industry. Seaweed farming in SE Asia is carried out by family-owned businesses which involve all working age members of the family, be it nuclear or extended family members, as compared with the WIO region. Five case studies of individual women are provided to show how they have been and continue to be the pillars of the seaweed farming industry. Economic gains from seaweed farming in both regions have provided positive and favourable changes in the quality of life (e.g. food, shelter, clothing, health care and social acceptance) of the family members involved. The case studies point to the commitment of women as the driving force of the seaweed industry, adding value to seaweeds, especially in the WIO. With such women spearheading the seaweed industry, the benefits will continue to be shared with whole families as well as other community members, as mothers are strong anchors of the families in many communities in developing countries.